Synthesis and electrochemical characteristics of isostructural LiMTiO4 (M = Mn, Fe, Co). Issue 7 (May 2017) - Luo, Minghe; Yu, Haoxiang; Lan, Hua; Yan, Lei; Qian, Shangshu; Ye, Wuquan; Shui, Miao; Long, Nengbing; Shu, Jie
Abstract: Isostructural LiMTiO4 (M = Mn, Fe, Co) have been successfully synthesized by a facile sol-gel route and evaluated their possibility as an anode materials for lithium ion batteries (LIBs). All the samples exhibit high operating potential plateaus (>1.7 V vs. Li + /Li), which can prevent the formation of the solid electrolyte interphase (SEI) film on the electrode surface effectively. In addition, electrochemical investigations show that LiCoTiO4 has a superior cycling performance, better rate capability, lower charge transfer resistance and higher lithium-ion diffusion coefficient than those of LiMnTiO4 and LiFeTiO4 . These electrochemical results indicate that LiCoTiO4 is the most promising lithium storage material among all the examined spinel-type LiMTiO4 samples.